Is the tax policy counter-cyclical in the Czech Republic? - Klusáčková, Hana; Pavel, Jan, 1978-; Vítek, Leoš, 1970-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2011)
Goal of this thesis is to evaluate the fiscal and tax policies in terms of pro-cyclicality and counter-cyclicality. The first three chapters deal with the theoretical part. In this part are issues such as fiscal and tax policy, national budget and various types of balances, the economic cycle and it's phases, the concept of counter-cyclical policy of economic theories and also the Pact of Stability and Growth and content of Convergence program of the Czech Republic. The practical part includes an analysis of these policies on the basis of the Czech Republic. The practical part includes an analysis of these policies on the basis of specific figures and evaluation of the results obtained.
Vedoucí práce: Jan Pavel
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: zdanění a daňová politika [obor bakal. práce]; bakalářské práce; bachelor's theses